MODEL PARTISIPASI PETANI LAHAN KERING DALAM KONSERVASI LAHAN - Suwarto Suwarto; Suwarto Suwarto; Sapja Anantanyu (Muhammadiyah University Press, 2012)
The study intends to describe the participation of farmers in the dryland crop based Land Conservation Index (LCI), describes the factors that affect the implementation of land conservation, and develop models to improve the participation of farmers in land conservation. Research carried out in Sub DAS upstream of Solo river. All of the food crop farmers from the Pundung villages totaling 68 family heads as respondents. The results of a study of farmers in conserving land at a moderate level. Model to improve the implementation of land conservation is increasing: land area, ownership ruminants, a family member who worked, and level of education, and empowerment to increase participation in land conservation in the parameter is still low, namely: planting plants to strengthen terracing, mulching or manure, planting annual crops on sloping land, crop rotation, and a sense of responsibility of farmers.